Predictors of extracapsular extension in HPV-associated oropharyngeal cancer treated surgically. (February 2017) - Geltzeiler, Mathew; Clayburgh, Daniel; Gleysteen, John; Gross, Neil D.; Hamilton, Bronwyn; Andersen, Peter; Brickman, Daniel
Highlights: The aim is to identify CT characteristics predictive of ECE. Three or more radiologically suspicious (RS) nodes has a 91% PPV for ECE. Severely irregular borders plus 3 (RS) nodes have a 92% PPV for ECE. Clinically N0 patients had a pathologic ECE rate of 3.3%. These measures are useful for counseling about the need for adjuvant therapy. Abstract: Objectives: Extracapsular extension (ECE) in cervical metastatic lymph nodes remains an indication for adding chemotherapy for patients with oropharyngeal squamous cell carcinoma (OPSCC). The aim of this study is to identify specific imaging characteristics on computed tomography (CT) scan that are predictive of ECE in order to better risk stratify patients preoperatively. Materials and methods: A single cohort study was performed using a prospectively collected database of patients with HPV-related OPSCC who underwent transoral robotic surgery with cervical lymphadenectomy. CT scans were assessed for the presence of multiple imaging characteristics, including lymph node size, number of nodes positive, cystic appearance, and border irregularity. Univariable and multivariable analyses were performed to analyze each variable's predictability of pathologic ECE. Results: 100 patients underwent TORS with cervical lymphadenectomy for OPSCC from 2010 to 2015. Ninety-one percent (21/23) of patients with 3 or more radiologically suspicious nodes were found to have pathologic ECE, which was a significantly greater proportion than patients with fewer suspicious nodes (p < 0.001). CT scans with 3 or more radiologically suspicious nodes displayed a sensitivity and specificity of 55% and 94%, respectively with a positive predictive value (PPV) of 91% for ECE. Irregular borders and age were also correlated with ECE on multivariable analysis. Conclusion and relevance: The presence of 3 or more radiologically suspicious lymph nodes on CT scan has a 91% PPV for any histologic evidence of ECE. The absolute number of radiographically suspicious lymph node metastases may be a useful method for risk-stratifying patients for the presence of ECE.